The Social Policy of the Second Polish Republic Towards Disabled People - Grata, Paweł (European Journal of Multidisciplinary Studies, 2021)
Problems of disable people were a very important social issue in the Second Republic of Poland. Social policy towards them was not unitary. It dealt with issues of war invalids (veterans and civilians), casualties of work accidents (who were insured) and poor disabled people (uninsured). A legal basis for these activities of the state and local governments was different and the support for the particular groups of disabled people was also various. The war invalids received more support than others. The help involved e.g. pensions, health care, prostheses and a chance to get a job. The casualties of work accidents received pensions and health care but their benefits were fewer than benefits for war invalids. Poor disabled people were in the worst position. The state, local governments, charity organisations tried to help them but their possibilities were too small in relation to the needs. Poor disabled people received neither benefits nor health care, they could not expect the help in retraining and finding a job and only few of them could count on a place in care facility (the number of these places was too small).